Improved fuzzy‐assisted hierarchical neural network system for design of computer‐aided English teaching system. (24th September 2020) - Li, Hui
Abstract: The world has enhanced the development of education with the rapid development of information technology in modern society to facilitate the information process. Educational technology has gained experience through the advancement of digital information network technology, from modern teaching technology to computer technology and communication technology. In this paper, an English learning system has been developed based on an improved fuzzy‐assisted hierarchical neural network system (IF‐HNNS). Improving the standard of English education is particularly important in improving intelligent education, especially the efficiency of classroom teaching. The development of an interactive educational system has changed the conventional way of teaching and facilitated individual independent learning. This English teaching system is a network updating computer‐aided learning platform. The computer‐aided system has the following advantages: (i) Easy‐to‐actualize computer‐aided learning media will provide more teaching content and teach satisfaction. (ii) The interaction of computer‐aided learning will raise interest in learning. (iii) Computer helped learners are rich in educational resources and are easy to set teaching goals. (iv) It will improve the monitoring of the education and teaching cycle using a computer‐aided learning with human‐computer interaction method.